Development of Hit The Mouse Games Using Javascript - Devi Perwitasari, Ika; Hendrawan, Jodi (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2023)
The idea of this game is that this game includes arcade games that are played traditionally which can be found in night markets or shopping centers such as Plazas. Arcade games are games that aren't focused on a story and can be entertaining when you're bored. This is done to analyze the needs that will be used to design and make a mole game, starting with determining the theme, game title, and programming language used to develop the game. The tools used include hardware and software. the application can run according to what has been designed by the author. The researcher tested the application by playing several times with different IP addresses as a test material for the application, whether the test was successful or not. Based on the results of making a game application for hitting moles, there are several conclusions that researchers can give, namely: a. This game can involve the player's concentration and become cognitive therapy, because the rats come out one by one from the ground to be hit. b. This game can only be played by one person. c. The making of the game Mole Hit has worked well according to the design that was made and compiled at the beginning of the game design, using the Javascript programming language.